Resveratrol restores insulin signaling and balances mitochondrial biogenesis and autophagy in streptozotocin-induced neurodegeneration in vitro - Varga, Kamilla; Sikur, Noémi; Paszternák, Alexandra; Friesenhahn, Anna-Lena; Zymela, Florian Emanuel; Bagaméry, Fruzsina; Tábi, Tamás; Wölfl, Stefan (European journal of pharmaceutical sciences, 2025)
Resveratrol, a natural phytoalexin, has been suggested to have beneficial effects in age-related diseases, including Alzheimer's disease. Studies indicate that it may delay memory decline and exert neuroprotective properties in vitro and in vivo. However, the precise mechanisms underlying these effects remain unclear, and the impact of resveratrol on central insulin resistance—a key feature of neurodegenerative disorders—remains insufficiently explored. Given the potential therapeutic significance of targeting insulin sensitivity in neurodegeneration, further investigation into the role of resveratrol in modulating these pathways is warranted. Our aim was to investigate the effects of resveratrol on insulin signaling and mitochondrial function in a previously established streptozotocin-induced in vitro neurodegeneration model. The phosphorylation status of key insulin signaling proteins and regulators of insulin resistance and autophagy markers were analyzed via Western blot and an ELISA-based microarray technique. The effects of resveratrol on mitochondrial biogenesis were evaluated through Mitotracker staining and quantification of mitochondrial mRNA and protein expression. Resveratrol augmented the cytoprotective effect of insulin in a concentration-dependent manner. It reduced the Ser(312) phosphorylation of IRS1, which is commonly linked to insulin resistance, and lowered the IC50 value for Tyr(895) phosphorylation required for activation. Similar insulin-sensitizing effects were observed in downstream signaling components. Resveratrol treatment exerted a caloric restriction mimetic activity through activating the AMPK/PGC1α/SIRT1 pathway and upregulated the expression of mitochondrial transcription factor TFAM and ATP synthase subunit (ATP5B). Despite the activation of mitochondrial biogenesis, the number of mitochondria was not altered, because it simultaneously induced autophagy marked by ULK1 phoshorylation and LC3 lipidation. Our findings indicate that resveratrol can enhance insulin signaling, even at the initial step of IRS1 phosphorylation. Its insulin-sensitizing effects extend beyond metabolic regulation to include survival responses. Resveratrol as a caloric restriction mimetic exerted a balanced effect on mitochondrial biogenesis and autophagy therefore improving mitochondrial quality control.